Genome Editing Technologies as Cellular Defense Against Viral Pathogens - Zhang, Yingzi; Li, Mo (Frontiers in Cell and Developmental Biology, 2021)
Viral infectious diseases are significant threats to the welfare of world populations. Besides the widespread acute viral infections (e.g., dengue fever) and chronic infections [e.g., those by the human immunodeficiency virus (HIV) and hepatitis B virus (HBV)], emerging viruses, such as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), pose great challenges to the world. Genome editing technologies, including clustered regularly interspaced short palindromic repeats (CRISPR)-CRISPR-associated (Cas) proteins, zinc-finger nucleases (ZFNs), and transcription activator-like effector nucleases (TALENs), have played essential roles in the study of new treatment for viral infectious diseases in cell lines, animal models, and clinical trials. Genome editing tools have been used to eliminate latent infections and provide resistance to new infections. Increasing evidence has shown that genome editing-based antiviral strategy is simple to design and can be quickly adapted to combat infections by a wide spectrum of viral pathogens, including the emerging coronaviruses. Here we review the development and applications of genome editing technologies for preventing or eliminating infections caused by HIV, HBV, HPV, HSV, and SARS-CoV-2, and discuss how the latest advances could enlighten further development of genome editing into a novel therapy for viral infectious diseases.